A cyclic enkephalin analog with high in vitro opiate activity. - DiMaio, J (1980)
A conformationally restricted analog of [Leu5]enkephalin was synthesized by cyclization of the COOH-terminal carboxyl group of leucine to the gamma-amino moiety of alpha, gamma-diaminobutyric acid (A2bu) substituted in position 2 of the peptide. Relative to [Leu5]enkephalin, the cyclic analog with D configuration in position 2, H-Tyr-cyclo(-N gamma-D-A2bu-Gly-Phe-Leu-), was 17.5 times more potent in the guinea pig ileum assay and twice as potent in the rat brain receptor binding assay, whereas its diastereomer H-Tyr-cyclo(-N gamma-L-A2bu-Gly-Phe-Leu-) showed low activity. The cyclic D isomer was also slightly more active than the open-chain reference compound [D-Nva2, Leu5]enkephalinamide in both assays, and it proved to be highly resistant to degradation by brain "enkephalinases." The steric constraints introduced in H-Tyr-cyclo(-N gamma-D-A2bu-Gly-Phe-Leu-) were shown to prevent the realization of most of the conformational features ascribed to linear enkephalin in solution or in the crystalline state and permitted an assessment of proposed models of the conformation of enkephalin when it is bound to the receptor.